Implementasi Ular Tangga Tradisional dan Media Buku Kerja Harian (ULTRA-MEDIA) pada Penderita Penyakit Kronis - Arief Andriyanto; Muhammad Sajidin; Emyk Windartik; Ima Rahmawati (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aims to enhance residents of Candirejo Hamlet, Mojokerto's understanding and skills in managing hypertension and diabetes mellitus by utilizing educational media, including Healthy Snakes and Ladders and a Daily Workbook. This program was implemented with an approach involving the participation of community service workers, students, cadres, and the community. Traditional games were modified into interactive learning tools that contained information on diet, physical activity, and medication adherence. A daily workbook was used to record participants' healthy lifestyle habits. A total of 30 participants participated in a series of activities, including education, game sessions, and blood pressure and random blood sugar checks. The results of the pre-post analysis showed an increase in self-care knowledge, as well as a decrease in average systolic blood pressure from 148 to 136 mmHg and random blood sugar levels from 198 to 170 mg/dL. This program has proven effective in increasing community engagement and health outcomes in the short term and is recommended for sustainable implementation in Posbindu and PKK as an educational model that prioritizes promotive and preventive aspects based on local culture